Tinjauan Teologis Tentang Penciptaan Langit dan Bumi Menurut Kejadian 1:1-2: Kajian Kedaulatan Tuhan - Paulus Kunto Baskoro; Jessi Darius; Earlyn Adi (STTII PURWOKERTO, 2023)
Doubting the existence of God as creator is a view that is often debated. As Christians, we must understand correctly that creation must be the center in order to hold a Biblical approach to Genesis 1:1-2. Living dependent on humas will only endanger faith in Christ. So it is very important that knowledge is also balanced with true knowledge about God. So that faith in God does not lead to destruction but more knowledge of God. The method used in research is descriptive qualitative. The purpose of the research is First, to examine and explain the principles of creation from the point of view of the truth of God’s Word. Second, it provides Biblical evidence regarding the principle of the creation of the heavens and the earth. Third, addirming the theological principle of the creation of the heavens and the eart is ideal in term of knowledge and evangelical truth